Life Table, Interspecific Competition, And The Influence Of Insect Growth Regulator On The Biology Of Cigarette Beetle, Lasioderma Serricorne (F.) (Coleoptera: Anobiidae) - Liew, Chiew Liang (2019)
The life table of Lasioderma serricorne (F.), interspecific competition between L. serricorne and Tribolium castaneum (Herbst), and Oryzaephilus surinamensis (Linnaeus), and the influence of methoprene and pyriproxifen on the biology of L. serricorne were investigated. Two strains of L. serricorne (USM and Japan strains) were reared under optimum conditions of 30 ± 2°C, 70 ± 5% relative humidity (r. h.), and 16-hour photoperiod. There was no significant difference (P 0.05) between the total development time for all immature stages, adult longevity, and lifetime fecundity per female of the USM and the Japan strains. There were also no significant differences (P < 0.05) between the two strains for population parameters n, instantaneous rate of increase; net reproductive rate; and T, mean generation time. L. serricorne was reared together in limited food source with T. castaneum and O. surinamensis to study the effect of interspecific competition between the three stored product beetles.